Contribution of Dehydration and Malnutrition to the Mortality of Children 0-59 Month of Age in a Senegalese Pediatric Hospital - Sylla, Assane; Keita, Younoussa; Diouf, Cheikh Sidate; Guéye, Modou; Mbow, Falilou; Ndiaye, Ousmane; Diouf, Saliou; Sall, Mohamadou Guélaye (International Journal of Child Health and Nutrition, 2014)
In-hospital mortality is an indicator of the quality of care. We analyzed the mortality of under five years children of Pediatric ward of Aristide Le Dantec teaching hospital to update our data, after an previous study conducted ten years earlier. Methods: This was a retrospective study involving children 0-59 months of age, hospitalized from January 1, 2012 to December 31, 2012. For each child, nutritional status was assessed according to 2006 World Health Organization growth standards; clinical and biological data were recorded. The outcome of the disease was specified. Bivariate and multivariable were used to identify risk factors for death. Results: 393 children were included. Overall mortality rate was 10% (39/393). Factors associated with death were severe wasting [OR = 8.27, 95% CI [3.79-18], male gender (OR = 2.98, 95% CI [1.25-7.1]), dehydration (OR = 5.4, 95% CI [2.54-13.43]) in the model using the weight-for- height z score, male gender (OR = 2.5, 95% CI [1.11-5.63]), dehydration (OR = 8.43, 95% CI [3.83-18.5]) in using the height- for- age z score, male gender (OR = 2.7, 95% CI [1.19-6.24]), dehydration (OR = 7.5, 95% CI [3.39-16.76]), severe underweight (OR = 2.4, 95% CI [1.11-5.63]), in the model using the weight-for- age z score, and male gender (OR = 2.5, 95% CI [1.11-5.63]), dehydration (OR = 8.43, 95% CI [3.83-18.5]) in that using MUAC. Dehydration and malnutrition are two independent factors of mortality. Our management protocols of dehydration and malnutrition have to be updated. Screening malnutrition has to be done systematically for each child by anthropometric measurements using WHO growth standards.